Penerapan Strategi Exchanging Viewpoint untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Matematika di Kelas IV Sekolah Dasar Negeri 013 Desa TG.Berulak Kecamatan Kampar Kabupaten Kampar - Heldanita Heldanita; Mimi Haryani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The research was motivated by the low of student’s learning achievement, this could be seen on the following indicators, in daily test, among 29 students, 13 students or 44.8% could achieved KKM specified, 16 students or 55.2% could not achieve it. The objective of research was to find out student’s learning achievement of mathematic. The formulation of research was how the implementation of exchanging viewpoint strategy to improve students’ learning achievement of mathematic for the fourth year students of state elementary school 013 Tanjung Berulak sub-district of Kampar the district of Kampar. The research was classroom action research consisted of for stages namely preparation of action, implementation of action, observation and reflection. The research was done in two cycles every cycle consisted of two meetings. The subject of research was fourth year students on school year 2014-2015 numbering 29 persons, and the object of research was the implementation of exchanging viewpoint strategy to improve students’ learning achievement. The data was collected using observation and test techniques. Data analysis technique was looking for the average and percentage and group it with its categories. The results of research has improved well than at prior action. At prior action students’ learning achievement was 44.82% or 13 students passed, at the first cycle 16 students passed or 55.17%. At the second cycle 23 students passed or the percentage was 79.31%. therefore the writer concluded that the implementation of exchanging viewpoint strategy to improve students’ learning achievement of mathematic for the fourth year students of state elementary school 013 Tanjung Berulak sub-district of Kampar the district of Kampar. Keyword: Implementation, Exchanging Viewpoint Strategy, Learning Achievement